2019
DOI: 10.21163/gt_2019.142.07
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Drought Around Chi Watershed During Ten-Year Period Using Terra/Modis Data

Abstract: To examine the drought affected area is highly challenging because the drought is a natural disaster that starts and expands slowly. The severity of the drought is different when the rainfall is imbalance in the area. The objective of this study was to analyze the drought around Chi watershed with total area of 49,131.920 km 2 by using data from Terra/MODIS satellite during 10 years (2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016). On part of method operation, the NDVI data was obtained from Terra/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…NDVI can be obtained from bringing near infrared wavelength and red visible wavelengths reflected from the earth's surface to calculate the difference of reflections. The values of NDVI will display in the range of -1 and +1, which can be calculated according to Equation 2 (Ogunode & Akombelwa, 2017;Rotjanakusol & Laosuwan, 2019). From Equation 2, it can be explained that the NDVI value approaching 0 means that the area is slightly covered with vegetation.…”
Section: Normalized Difference Vegetation Index (Ndvi)mentioning
confidence: 99%
“…NDVI can be obtained from bringing near infrared wavelength and red visible wavelengths reflected from the earth's surface to calculate the difference of reflections. The values of NDVI will display in the range of -1 and +1, which can be calculated according to Equation 2 (Ogunode & Akombelwa, 2017;Rotjanakusol & Laosuwan, 2019). From Equation 2, it can be explained that the NDVI value approaching 0 means that the area is slightly covered with vegetation.…”
Section: Normalized Difference Vegetation Index (Ndvi)mentioning
confidence: 99%
“…To examine the drought affected area is highly challenging because the drought is a natural disaster that starts and expands slowly. The severity of the drought is different when the rainfall is imbalance in the area (Rotjanakusol & Laosuwan, 2019). Based on the hydrological cycle, to prevent the reduction of groundwater face as a result of forest immaterial and the presence of trenches and open channels, control is required.…”
Section: Step 1: Identification and Analysis Canal Sitementioning
confidence: 99%
“…In addition, many research studies currently focus on developing a method to detect the land surface temperature using remote sensing technology. Remote sensing technology is accepted as being modern and efficient, and it can be applied to rapidly monitor and detect global phenomena (Uttaruk & Laosuwan, 2018;Rotjanakusol & Laosuwan, 2019;Uttaruk & Laosuwan, 2020). In the meantime, many research papers have indicated using a mathematical model in conjunction with remote sensing technology to analyse the land surface temperature, such as radiative transfer equation (RTE), Mono-Window (MW), split window (SW), Dual-Angle (DA) and single-channel (SC) (Ren et al, 2011;Yu et al, 2014;Chen et al, 2015;.…”
Section: Introductionmentioning
confidence: 99%